Perspectives on Product Stewardship - Cassel, Scott (Bernan Press, 2023)
Keywords: dept.mgt

Business succession planning: a vital component to the success and longevity of small businesses - Smith Jr, Robert A.; Badr, Kauther S. (International Academy of Business Disciplines 24th Annual Conference, 2023)
Keywords: dept.mgt

Cash Holdings and Firm Performance in the Restaurant Industry - Kim, Jung Hoon; Lim, Jaeseong; Ahn, Jin Sun; Kim, Youngbin (Journal of Applied Business and Economics, 2023)
This study explores the link between cash holdings and performance outcomes in public restaurant companies in the United States, leveraging the critical role played by the industry context. We hypothesize that cash holdings have positive associations with both short-term and long-term firm performance in the restaurant industry. Our empirical analyses, based on fixed-effect regression models that control for all time-invariant variables, reveal that holding cash can improve performance in the restaurant industry, in support of our hypotheses.
Number: 3
Keywords: dept.mgt; firm performance; peer-reviewed

Towards an integrated understanding of art, spirituality, and well-being - Yang, Charlie (Journal of Management, Spirituality & Religion, 2023)
Keywords: dept.mgt; peer-reviewed

The Escalating Competition Faced by Netflix - Jin, Sun Ahn; Jung, Hoon Kim; Youngbin, Kim; Jaeseong, Lim (Journal of Accounting-Business dan Management, 2023)
Num Pages: 1
Keywords: dept.mgt; peer-reviewed

The Effect of Market-Entry Timing on a Firm’s Speed and Cost of Entry - Lee, Minjae (American Journal of Management, 2023)
This paper examines the effect of market-entry timing on a firm’s speed and cost of entry in a setting where a firm needs to build a plant for market entry. Based on our developed analytical model, we provide seven scenarios of the market-entry timing effect on a firm’s entry speed and cost. We test hypotheses in the liquefied natural gas (LNG) industry. We use Wooldridge’s three-step instrumental variable (IV) approach to account for endogeneity bias. We find that a late entrant has (1) a shorter time-to-build and (2) a higher cost-to-build relative to an early entrant. Further, (3) the late entrant positively moderates the negative relationship of time-to-build and cost-to-build (i.e., the negative relationship of time-to build and cost-to-build becomes less negative for the late entrant). These empirical results are consistent with the prediction of when both revenue effect (i.e., revenue curve shift) and cost effect (i.e., cost curve leftward shift) exist.
Number: 3
Keywords: dept.mgt; peer-reviewed; time compression diseconomies

Developing the Construct of Speed Ceteris Paribus - Lee, Minjae (Academy of Management Proceedings, 2023)
Firm speed has long been a construct of interest among managers and researchers. Despite its importance, making a ceteris paribus comparison of speed can be challenging. In the current paper, we suggest an alternative to the conventional way of capturing the speed ceteris paribus. First, we illustrate the concept of faster speed in strategic management research. Second, we use numerical simulation data to illustrate the challenges of the conventional methodology, known as the nonlinear transformation of variables. We show that this method is difficult to apply and may produce an inaccurate measurement of the concept unless the exact functional form is chosen. Third, we suggest an alternative methodology, known as data envelopment analysis. This accounts for the challenges of the conventional methodology when we do not know the accurate functional form for nonlinear transformation, while performing as well as the best of the conventional approach. Finally, by using actual firm data, we show that our suggested methodology can be an effective alternative to the conventional approach of capturing a firm’s speed.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Research Methods; dept.mgt

When Does an Increase in a Firm’s Operational Effectiveness Reduce its Economic Performance? - Lee, Minjae (Academy of Management Proceedings, 2023)
Conventional wisdom suggests that an increase in a firm’s operational effectiveness will increase its economic performance. However, we show that an increase in a firm’s operational effectiveness can decrease its economic performance. Specifically, a firm’s increase in operational effectiveness of its existing projects following a positive demand shock can limit its profitable growth as its strategic resources are not allocated to pursuing new projects, thereby incurring opportunity costs that can lower its economic performance. We corroborate this reasoning in the context of the liquefied natural gas industry, which experienced a positive demand shock in 2000 due to energy market liberalization. We find empirically that a firm’s operational effectiveness increases its Tobin’s Q in the pre-shock period and reduces it in the post-shock period.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Strategic Management; dept.mgt

Understand the changes in motivation: comparative studies using theory-based interventions - Wang, Zheni; Briand, Melanie (Academy of Management Proceedings, 2023)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to manage the daily routine of motivational dynamics at work. This research answered how self-determination-theory-based interventions change employees’ motivation and motivational consequences during short time frames (i.e., within an hour, within a few weeks/months). Field study one focused on assessing the effectiveness of a one-day training workshop in helping improve managers’ work motivation, basic psychological needs satisfaction/frustration, and changing managers’ needs-supportive/thwarting behaviors within a few weeks. Results supported the training effectiveness as managers were rated less needs-thwarting by their direct subordinates and self-reported improvement in needs satisfaction/frustration six weeks after completing the training program. Online study two used the mean and covariance structure analysis and tested the three types of basic psychological needs supportive/thwarting and control conditions (3x2x1 factorial design) on the situational motivation, vitality, and general self-efficacy for playing online word games within 30 minutes. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group means comparison results showed consistently lower controlled motivation across the needs-supportive and thwarting experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in Amazon MTurk participants. Supplementary structural equation modeling (SEM) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications on employee training and organizational change programs, and the limitations.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizational Behavior; dept.mgt

What explains the spread of corporate social responsibility? The role of competitive pressure and institutional isomorphism in the diffusion of voluntary adoption - Han, Seungmin; Ito, Kiyohiko (Journal of Management & Organization, 2023)
This study provides a new perspective on the determinants of the spread of voluntary corporate social responsibility (CSR) adoption by incorporating the potential role of its adoption by industry competitors. We find supportive evidence that firms make CSR adoption decisions in response to competitive pressure as well as institutional mimetic pressures. Based on an event history analysis of longitudinal data from a sample of 711 Korean publicly traded firms over a 12-year period, our findings suggest that the CSR behavior of competitors is positively associated with a focal firm's earlier adoption of CSR, leading to the diffusion of CSR across firms. Specifically, this study shows that the pure rivalry-driven pressure from non-leader competitors has a stronger positive relationship with earlier CSR adoption. The results also indicate that a firm's CSR adoption decision is accelerated by competitive rivalry as well as social pressures arising from institutional mimetic isomorphism.
Keywords: Competitive strategy; corporate social responsibility; dept.mgt; institutional theory; peer-reviewed; quantitative methods

Arts-based pedagogy in management education: personal reflections - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (Honing Self-Awareness of Faculty and Future Business Leaders: Emotions Connected with Teaching and Learning, 2023)
Historically business education has put greater emphasis on rational analysis and the acquisition of instrumental and technical knowledge, while paying relatively scant attention to developing business students’ soft skills such as self- and social awareness and emotional intelligence through contemplative learning. In light of the growing need for more open and diverse ways of knowing that are more holistic, emotional, and aesthetic in management education, the authors present a 2 × 2 framework of arts-based pedagogy which helps organize various arts-based practices currently used in management education. The authors also share their personal reflections on using artful practices, specifically focussing on two individual-level experiential learning activities (i.e. museum visits and e-portfolio projects) and one group-based participatory art project. The authors further discuss why creative thinking and innovative arts-based practices can open up a new possibility for filling the gaps in current management education, especially in regard to developing students’ self- and social awareness and environmental consciousness in a more creative manner.
Keywords: Arts-based pedagogy; Digital photography; Electronic portfolio (e-portfolio); Museum learning; Participatory art; Socially engaged art; dept.mgt

Thriving in the dynamics: a multi-level investigation of needs-supportive features, situational motivation, and employees’ subjective well-being - Wang, Zheni; Panaccio, Alexandra (Current Psychology, 2023)
Employees often demonstrate various regulatory intentions toward multiple responsibilities they must fulfill on the job. Therefore, it is possible that employees’ motivation changes during the workday because of the various situations they have experienced and that these motivational fluctuations affect their subjective well-being across different activities. Following the integrated frameworks of the self-determination theory (SDT) and the hierarchical model of motivation (H-SDT), the present research studied the variations of employees’ daily motivation for work across different activities using the survey of day reconstruction method (DRM). Multi-level structural equation modeling (MSEM) was used to analyze the variations in the perceived three basic psychological (i.e., autonomy-, relatedness-, and competence-) needs-supportive features (NSFs), situational motivation, and variables capturing the employees’ subjective well-being (including vitality and positive/negative affect) laid out according to a list of work episodes in DRM. Results of this study confirmed that employees’ subjective well-being (mainly vitality and positive affect) were positively promoted by NSFs pertained to specific work activities via the indirect path of situational autonomous motivation at work. Furthermore, vitality and positive affect were also directly predicted by situational autonomous motivation. These empirical findings expanded the research evidence supporting employees’ subjective well-being as a multi-level and multi-dimensional dynamic motivational consequence promoted by configurable specific NSFs at work. We also discussed the limitations and future directions for this line of research.
Keywords: Dynamics of work motivation; Multi-level modeling; Psychological health; dept.mgt; peer-reviewed